Migración e identidad: una experiencia desde la ilegalidad - Aguilar Edwards, Andrea (Comparative Cultural Studies: European and Latin American Perspectives, 2018)
The article addresses the life experience of a Mexican immigrant family after twenty years living in the United States illegaly. The information is recorded from the father’s testimony. The interview technique was used from a phenomenological approach that allows us to analyze the relationship between identity, culture and territory as related factors. The results highlight the existence of an emerging identity in which individuals transform the way they perceive themselves, others and the world around them, as a result of interactions in a disadvantaged social position. The need for a migration policy that guarantees the human rights of immigrants is pointed out.